Amelioration of Experimental Autoimmune Encephalomyelitis Using the Myelin Oligodendrocyte Glycoprotein35-85 Peptide - (:unkn) unknown (My University, 2012)
Multiple sclerosis (MS) is a chronic debilitating disease affecting the central nervous system (CNS) in humans. Experimental autoimmune encephalomyelitis (EAE) remains the primary animal model of MS. MS/EAE are considered to be autoimmune diseases mediated by CD4+ T helper (TH) cells. The role of B cells and antibody is under debate. Previous studies established B cell dependent (induced with recombinant myelin oligodendrocyte glycoprotein, [rMOG]) and B cell independent (induced with the MOG35-55 peptide) animal models of EAE. The identification of a unique B cell epitope (MOG amino acids [aa] 46-85) preceding the identified protective epitope (MOG61-85) led to the hypothesis that these antibodies against MOGaa46-85 were important in epitope selection in the rMOG model of EAE. Co-immunization of WT and B cell deficient (B cell-/-) mice with MOG35-55 and MOG61-85 resulted in abrogation (B cell-/- mice) or amelioration (WT mice) of EAE. Thus, mice were immunized with MOG35-85 peptide and observed for EAE induction. Absence of EAE in WT and B cell-/- mice was observed. These results confirmed the protective nature of the MOG61-85 peptide but did not support a role for antibodies to MOG¬46-85 in the selection of the protective epitope. Mechanistic studies revealed decreased production of the pro-inflammatory cytokines, interferon (INF) γ and interleukin (IL) 17, when immune cells were primed to MOG61-85 in vivo. Furthermore, using IL10 deficient (IL10-/-) mice, it was demonstrated that IL10 was important in EAE incidence, but not in disease severity, in the presence of the MOG61-85 epitope. Flow cytometric analysis of spleen cells from these mice demonstrated an increase in the number of T cells expressing FoxP3 expression and an increase in the CD4+ CD25+ T cell population, but a comparable level of CD4+ T regulatory (Treg) cell population. In addition no changes could be detected in the CD8+ T cell population. These experiments provide a deeper understanding of the B cell-dependent, rMOG model of EAE, demonstrating the role of the MOG61-85 epitope in down-regulating the pro-inflammatory response leading to protection from EAE, perhaps mediated by CD4+ Treg cells.
Keywords: B Cells and Antibody; Experimental Autoimmune Encephalomyelitis; Multiple Sclerosis